Service-learning : the essence of the pedagogy - Furco, Andrew; Billig, Shelley (Advances in service-learning research., 2002)
The Advances in Service-Learning Research book series was established to initiate the publication of a set of comprehensive research volumes that would present and discuss a wide range of issues in this broad field called service-learning. Service-learning is a multifaceted pedagogy that crosses all levels of schooling, has potential relevance to all academic and professional disciplines, is connected to a range of dynamic social issues, and operates within a broad range of community contexts. In terms of research, there is much terrain to cover before a full understanding of service-learning can be achieved. This volume, the first in the annual book series, explores various themes, issues, and answers that bring us one step closer to understanding the essence of service-learning.The chapters of this volume focus on a broad range of topics that address a variety of research issues on service-learning in K-12 education, teacher education, and higher education. Through a wide-scoped research lens, the volume explores definitional foundations of service-learning, theoretical issues regarding service-learning, the impacts of service-learning, and methodological approaches to studying service-learning. Collectively, the chapters of the book provide varying and, at times, opposing perspectives on some of the critical issues regarding service-learning research and practice.